2001
DOI: 10.1007/s005350170049
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of latently infected hepatitis B virus in a leukemia patient with antibodies to hepatitis B core antigen

Abstract: A 66-year-old man with chronic B-cell leukemia who had antibody to hepatitis B core antigen (anti-HBc) but not hepatitis B surface antigen (HBsAg) suffered from lethal hepatitis caused by hepatitis B virus (HBV) reactivation. He initially lacked circulating viral genomes in his sera and did not have a past history of liver dysfunction. In this patient, the immunosuppressive condition introduced by disease progression of leukemia induced reactivation of dormant HBV, and the withdrawal of chemotherapy resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Reactivation of hepatitis B is a well-documented complication of tumor chemotherapy and immunosuppressive treatments, being observed both in patients with overt hepatitis B (HBsAg seropositive) as well as in those with occult infection (HBsAg seronegative) (Dhedin et al, 1998;Ma et al, 2003;Marusawa et al, 2001;Seth et al, 2002). Occult HBV infection is likely to be more common than previously recognized and to bear important clinical consequences (Raimondo et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Reactivation of hepatitis B is a well-documented complication of tumor chemotherapy and immunosuppressive treatments, being observed both in patients with overt hepatitis B (HBsAg seropositive) as well as in those with occult infection (HBsAg seronegative) (Dhedin et al, 1998;Ma et al, 2003;Marusawa et al, 2001;Seth et al, 2002). Occult HBV infection is likely to be more common than previously recognized and to bear important clinical consequences (Raimondo et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…[13][14][15] Furthermore, reactivation of apparently cured HBV infection has been described under chemotherapy or immunomodulating therapy after renal and bone marrow transplantation, and in some of these cases a reverse seroconversion from anti-HBs to HBsAg has been observed. [16][17][18][19] The residual risk of posttransfusion HBV infection has been calculated by several groups in the United States and Germany on the basis of HBV incidence data and the duration of the early window period until HBsAg becomes detectable to be 1:63 000 and less than 1:100 000 blood donations, respectively. 20,21 It has been shown that blood donations of HBsAg-and anti-HBs-negative but anti-HBc-positive HBV carriers can cause posttransfusion hepatitis B.…”
Section: Introductionmentioning
confidence: 99%
“…Occult HBV carriers can develop HBV reactivation and liver dysfunction under certain immunosuppressive conditions [69,70]. The formation of covalently closed circular DNA is considered due to the persistent HBV infection in hepatocytes in individuals after seroconversion from HBsAg to anti-HBs [71].…”
Section: Introductionmentioning
confidence: 99%